MENINGKATKAN TANGGUNG JAWAB SISWA DALAM MELAKUKAN SESUATU BERDASARKAN PENJELASAN SECARA LISAN TEMA LINGKUNGAN DENGAN METODE DEMONSTRASI DI KELAS III SDN KEPUH KLAGEN WRINGINANOM GRESIK - Suwanti (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2018)
Thematic learning as a learning model includes one type or type rather than an integrated learning model. The problem of students' responsibility in doing something based on verbal explanations of environmental themes with demonstration methods in researched schools that solving problems is urgently needed. This study aims: 1) Describe the activities of the teacher in increasing the responsibility of students in doing something based on an explanation orally the theme of the environment with a demonstration method in Class III SDN Klagen Wringinanom Gresik. 2) Describing the activities of students in learning activities increases the responsibility of students in doing something based on an explanation orally the theme of the environment with the demonstration method in Class III of SDN Klagen Wringinanom Gresik. 3) Describe learning with demonstration methods in increasing students' responsibility in doing something based on verbal explanations of environmental themes in Class III of Kepuh Klagen SDN Klagen Wringinanom Gresik. This research is a classroom action research conducted collaboratively. Designing problem situations, and ways to collaborate with children, is the main focus of meetings that occur between teachers and researchers. This research was carried out at the Kepagen Klagen Wringinanom Gresik Elementary School with the address Bureng Kidul, Kepuhklagen, Kec. Wringinanom, Gresik Regency, East Java 61176. The subjects of this study were Class III students of 25 children. The study was conducted in odd semester 2018/2019 academic year, for 3 months (August, September and October 2018)). Procedures for cyclical action research are: 1) planning, 2) implementation, 3) observation, and 4) reflection, through a series of cycles. Data collection through observation (observing), artifacts and documents (testing) and nonstandard tests. Test instrument items with validity test, reliability test, calibration test (level of difficulty) and distinguishing test. the entire process of data analysis is interactive using the Miles and Huberman models with the final mix method analysis. The results of the study concluded: 1) Teacher's activity experienced an increase in Pre-Action obtaining 65 percent and increasing in Cycle I by 78.57 percent and increasing in Cycle II by 88.57 percent; 2) Student activity has increased in Pre-Action to get 47.86 percent and increase in Cycle I by 66.43 percent and increase in Cycle II by 86.43 percent; 3) The average value of the test (Classical Absorption) has increased in Pre-Action to get a result of 75.2 percent and increase in Cycle I by 78.6 percent and increase in Cycle II by 85.4 percent. Classical Learning Completion has increased in Pre-action gets 64 percent and increases in Cycle I by 80 percent and increases in Cycle II by 84 percent.